Energy and tannin extract supplementation for dairy cows on annual winter pastures - Alves T.P. (2017)
Energy supplementation can increase the consumption of metabolizable energy and substrate for microbial growth, while condensed tannins aid in increasing the duodenal flow of metabolizable proteins. The objective of this study was to evaluate the effects of energy supplementation and the inclusion of tannin extract (TE) from Acacia mearnsii (Weibull Black, Tanac S. A., Montenegro, Brazil) on the production performance of dairy cows grazing on winter pastures. Nine multiparous Holstein cows in mid lactation were distributed in a 3 × 3 Latin square experimental design over three periods of 28 days (21 adaptation and 7 sampling). The treatments were: without supplementation (WS), supplementation with 4 kg of corn grain (CG), and corn grain + 80 g of tannin extract (TE). The dry matter (DM) intake from pastures was similar among treatments, but the consumption of DM of the supplement was higher in the CG treatment than that in the TE treatment. The total DM intake was higher for the supplemented animals (17.3 kg·day-1) than that for the unsupplemented animals (14.9 kg·day-1) and in the TE treatment (17.7 kg·day-1) than in the CG treatment (16.7 kg day-1). Milk production increased from the unsupplemented to the supplemented animals (20.9 to 23.5 kg, respectively), while the content of urea N in the milk decreased (12.6 to 10.5 mg·100 mL-1, respectively). There were no differences in milk production or content of milk urea N between the CG and TE treatments. Energy supplementation is a tool for improving the nutritional profile and the performance of dairy cows in mid lactation grazing on annual winter pastures, while tannin extract AIDS in improving the energy balance.